2011
DOI: 10.1590/s0102-33062011000100017
|View full text |Cite
|
Sign up to set email alerts
|

Levantamento da flora apícola em Santa Luzia do Paruá, Sudoeste da Amazônia, Maranhão

Abstract: RESUMO(Levantamento da flora apícola em Santa Luzia do Paruá, Sudoeste da Amazônia, Maranhão). Foi realizado o levantamento das plantas visitadas por Apis mellifera L. através de análise polínica no município de Santa Luzia do Paruá, Maranhão, localizado a noroeste do Estado, em região amazônica. A temperatura média anual varia entre 26 °C e 27 °C, com umidade relativa do ar anual entre 79 a 82% e precipitação pluviométrica entre 2000 a 2400 mm anuais. O estudo foi conduzido entre agosto de 2005 e julho de 200… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
11

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 13 publications
0
11
0
11
Order By: Relevance
“…Studies on abdominal nectar (Absy et al, 1980), stored pollen (Absy et al, 1984), corbicular pollen (Marques-Souza et al, 1993, 2007 and honey (Marques, Muniz, Lopes, & Silva, 2011) in this region indicated the presence of this pollen type in the samples. Silva, Secco, and Lobo (1996) reported that Africanised bees intensively visited B. verticillata flowers in Serra de Carajás, Pará State, especially during the periods of transition between the dry and rainy seasons.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…Studies on abdominal nectar (Absy et al, 1980), stored pollen (Absy et al, 1984), corbicular pollen (Marques-Souza et al, 1993, 2007 and honey (Marques, Muniz, Lopes, & Silva, 2011) in this region indicated the presence of this pollen type in the samples. Silva, Secco, and Lobo (1996) reported that Africanised bees intensively visited B. verticillata flowers in Serra de Carajás, Pará State, especially during the periods of transition between the dry and rainy seasons.…”
Section: Discussionmentioning
confidence: 87%
“…Although Cecropia species are considered anemophilous, masking the real nectar sources exploited by bees, when this pollen type is found in honey, it can provide information on the conservation status of the study area and data on the geographical origin of the honey (Oliveira, 2009). A high frequency of Cecropia pollen was found in the honey spectra from A. mellifera in the states of Bahia (Oliveira, 2009) and Maranhão (Marques et al, 2011). Sosa-Nájera et al (1994) included Cecropia obtusifolia Bertol.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The richness of the flora and floristic composition is partially known through phytosociological surveys of tree species, studies on flowering and fruiting patterns of trees and inventories of bee flora and Orchidaceae (Muniz 1998(Muniz , 2008(Muniz , 2011Silva et al 1999;Marques et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Para a apicultura (criação racional de Apis mellifera) e meliponicultura (criação racional de abelhas-sem-ferrão), o conhecimento da flora apícola proporciona a verificação das particularidades dos ecossistemas em que essas atividades são desenvolvidas, estabelecendo potencial produtivo e definição das possibilidades de manejo, considerando-se que a variabilidade da flora permite uma apicultura ou meliponicultura sustentáveis e rentáveis (MARQUES et al, 2011).Os estudos palinoló-gicos também são usados na avaliação da qualidade do mel (melissopalinologia) (BARTH, 1989). No Brasil, o controle de qualidade de méis restringe-se à análises microbiológicas e físico-químicas, mas diversos laboratórios já realizam aná-lises palinológicas de mel (OSTERKAMP; JASPER, 2013).…”
Section: Palinologia E a Interação Plantas-polinizadoresunclassified